Biomedical and textile applications of Alternanthera sessilis leaf extract mediated synthesis of colloidal silver nanoparticle - Kabeerdass, Nivedhitha (2023)
The aqueous extract of Alternanthera sessilis (As) acts as the precursors for the quick reduction of silver ions, which leads to the formation of silver nanoparticles. In the agar, well diffusion method of the Klebsiella pneumoniae shows the minimal inhibitory concentration of 12 mm against A. sessilis mediated silver nanoparticles (As-AgNPs) at 60 µg/mL concentration. Fabric treated with novel AS-AgNPs is tested against the K. pneumoniae and shows an inhibitory action of 12 mm with mixed cotton that determines the antimicrobial efficacy of the fabrics. Uv- visible spectrophotometer was performed, showing a surface plasmon resonance peak at 450 nm cm-1. FTIR shows the vibration and the infrared radiation at a specific wavelength of 500-4000 cm-1. The HR-TEM analysis showed the presence of black-white crystalline, spherical-shaped As-AgNPs embedded on the fabrics range of 15 nm-40 nm. In the scanning electron microscope, the presence of small ball-shaped As-AgNPs embedded on the fabrics at a voltage of 30 KV was found with a magnification of 578X. EDAX was performed in which the nanoparticles show a peak of 2.6-3.9 KeV, and it also reveals the presence of the composition, distribution, and elemental mapping of the nanoparticles. The cytotoxic activity of synthesized nanosilver was carried out against L929 cell lines, which show cell viability at a concentration of 2.5 µg mL-1. Cell proliferation assay shows no cytotoxicity against L929 cell lines for 24 h. In this study, the green synthesis of silver nanoparticles from A. sessilis appears to be a cheap, eco-friendly, and alternative approach for curing infectious ulcers on the floor of the stratum corneum. Nanotechnology conjoined with herbal therapeutics provides a promising solution for wound management.